Transient response of rotary desiccant wheel and affecting factors of noumenal parameters - Hao, Hong; Feng, G.; Wang, H.; Li, G.; Yu, L. (2011)
The paper presents a research with the aim to make the dynamic response of the rotary desiccant wheel fit with the variable air rate of VRV air conditioning system and save more energy. Mathematical model of rotary desiccant wheel which can transfer heat and mass is established. The test stand which is to study the transient response rules of rotary desiccant wheels under the VAV operation conditions is set up to make simulation and to carry out experimental study. Results demonstrate that when process air volume step decreases, process outlet relative humidity ratio decreases with time increasing. When the temperature increases, the regeneration outlet temperature will increase slightly while the relative humidity ratio will decrease slightly. When process air volume step increases, process outlet relative humidity ratio increases with time decreasing. When the temperature decreases, the regeneration outlet temperature and relative humidity ratio decreases and increases a little accordingly, and the response time is about 1 h. Analog results show that with the increase of thickness, wheel speed and specific heat of material, the difference between new stable value and initial value of process outlet humidity ratio reduces and the difference value of process outlet temperature increases. When the process air volume increases suddenly, response time of step is less than that of step decreases. The analog results also demonstrate that the sensible heat load could be reduced by more than 20% through variable air volume, and could be reduced another 13% with changing regeneration temperature or flow rate. The energy consumption of the system will be significantly reduced to save more energy.